ECONOMICS TEACHER CLASS MANAGEMENT AND PARENTAL SUPPORT IMPACT ON STUDENT LEARNING MOTIVATION (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
AbstractClassroom management is an effort carried out by the person in charge of teaching and learning activities or assisting in achieving optimal conditions so that learning activities can be carried out as expected. This study aims to determine the effect of the management of the economics teacher class and parental support on students' learning motivation in classes X-A and X-B at MAN 5 Jombang in the 2022/2023 academic year. The sample used was 52 students. Data collection techniques used are observation, questionnaires, interviews, and documentation. Data analysis using multiple regression linear regression model. The results of the study obtained that the t count in the management of the economics teacher class showed tcount> ttable = 2,591 > 1,671 significance 0.000 < 0.05 and parental support showed tcount> ttable = 1.890 > 1.671 significance 0.000 < 0.05. While the results of the analysis of the coefficient of determination concluded that the Class Management (X1) and Parental Support (X2) variables had a significant positive effect on student motivation, with the results of the regression analysis showing Fcount> Ftable = 5.857 > 3.190 with a significance of 0.000 < 0.05. This research uses multiple linear regression model data analysis to determine the magnitude of the influence of classroom management and parental support on students' learning motivation with a combination of variables X1, X2, and Y, which has never been done.